2023
DOI: 10.1002/jcp.31060
|View full text |Cite
|
Sign up to set email alerts
|

The origin, progress, and application of cell‐based cardiac regeneration therapy

Abstract: Cardiovascular disease (CVD) has become a severe threat to human health, with morbidity and mortality increasing yearly and gradually becoming younger. When the disease progresses to the middle and late stages, the loss of a large number of cardiomyocytes is irreparable to the body itself, and clinical drug therapy and mechanical support therapy cannot reverse the development of the disease. To explore the source of regenerated myocardium in model animals with the ability of heart regeneration through lineage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 214 publications
(250 reference statements)
0
2
0
Order By: Relevance
“…Nevertheless, a tangible clinical association of heart self-renewal with cardiac stem cells or EPCs has not been identified [99,100]. Therefore, despite the probable presence of a physiologic cardiac stem cell repair mechanism, the clinical significance of such a natural endogenous restorative capacity of the heart remains questionable [17,18]. rather than the differentiation of progenitor cells, is the main source of cardiomyocyte renewal [98,99].…”
Section: Endogenous Stem Cell Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, a tangible clinical association of heart self-renewal with cardiac stem cells or EPCs has not been identified [99,100]. Therefore, despite the probable presence of a physiologic cardiac stem cell repair mechanism, the clinical significance of such a natural endogenous restorative capacity of the heart remains questionable [17,18]. rather than the differentiation of progenitor cells, is the main source of cardiomyocyte renewal [98,99].…”
Section: Endogenous Stem Cell Differentiationmentioning
confidence: 99%
“…Nevertheless, a study later demonstrated that these EPCs may originate from a niche in the vessel wall rather than from the bone marrow [16]. Although such endogenous restorative mechanisms, as well as current medical and mechanical therapeutic approaches, may decelerate disease progression, they cannot reverse its pathological changes [17,18]. Therefore, the idea that stem cells with regenerative potential may be utilized for treating cardiac diseases such as myocardial infarction and heart failure has sparked great interest in their potential clinical applications [19][20][21].…”
Section: Introductionmentioning
confidence: 99%